Kinerja Karyawan Bagian Produksi Ditinjau Dari Motivasi dan Disiplim Kerja Karyawan PT. SOMIN Surakarta Tahun 2015 - Asmono, Oktavia Farida; , Drs. Nur Chusni, SE, M.Ag (2015)
Oktavia Farida Asmono. A210110089. Economic Accounting Study Program. The Faculty of Education, University of Muhammadiyah Surakarta, 2015. The purpose of this study was to determine: 1) To determine the effect of employee motivation on the performance of the production employees at PT. SOMIN Surakarta year 2015. 2) To determine the effect on the performance of employees disciplined production employees at PT. SOMIN Surakarta Year 2015. 3) To determine the influence of motivation and discipline on the performance of the production employees at PT. SOMIN Surakarta 2015. This research is quantitative research with the associative drawing conclusions through statistical analysis. The population in this study were all employees at PT. SOMIN Surakarta. The population is taken as many as 40 employees. The necessary data and documentation obtained through a questionnaire. Questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, F test, t-test, R2, and the relative contribution and effective. Results of regression analysis to obtain the regression line equation: Y = 4.907 + 0, 260 X1 + 0, 342 X2. The equation shows that the performance of employees affected by motivation and discipline. The conclusions drawn are: 1) "There is a motivational effect on the performance of employees working in the production department of PT. SOMIN Surakarta 2015 "unacceptable. It is based on multiple linear regression analysis (t-test) is known that t count> t table, namely 2.060> 2.042 and the significance value <0.05, namely 0.046 with the effective contribution of 20.4%. 2) "There is a disciplinary effect on the performance of employees working in the production department of PT. SOMIN Surakarta 2015 "unacceptable. It is based on multiple linear regression analysis (t-test) is known that t count> t table, namely 3.435> 2.042 and the significance value <0.05, namely 0.001 with the effective contribution of 37.1%. 3) "There is the influence of motivation and discipline of work on the performance of the production employees at PT. SOMIN Surakarta 2015 "unacceptable. It is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 25.057> 3.320 and the significance value <0.05, namely 0.000. 4) The result of the coefficient of determination (R2) of 0.575 indicates that the influence of motivation and discipline work together on employee performance of production at PT. SOMIN Surakarta 2015 amounted to 57.5%, while 42.5% is influenced by other variables not examined. Keywords: motivation, discipline and employee performance.